Analysis of Factors Affecting Demand for Murabahah Financing at Baitul Mal Wat Tamwil Waashil Medan - Alfi Khairi (IHSA Institute, 2022)
The title of this research is “Analysis of Factor Influencing Demand of costing Murabahah At BMT Waashil Medan.” This research uses 50 member's to costing murabahah as samples. The object of this research is to know the influence of administration cost, melting point speed costing and advantage to demand of costing murabahah at BMT Waashil Medan. This research uses linear regression analysis model, existing data processed by using computer program of SPSS 12. Results of hypothesis show increasing administration cost, melting point speed costing and advantage to demand of murabahah expenses at BMT Waashil Medan. Given the influence among variables, Ordinary Least Square method used to estimate. Result of estimation show administration cost, melting point speed costing and advantage to demand of costing murabahah.